Peto’s paradox: 2 problems 2 answers - Uzoigwe, Chika Edward (Frontiers in Ecology and Evolution, 2025)
Peto’s paradox throws down the gauntlet to researchers to explain why larger animals have the same cancer risk as more diminutive species, notwithstanding the much higher cellularity of the former. Any explanation of the paradox must also contend with the fact that larger animals have a greater longevity and thus longer for their greater number of cells to undergo mutagenesis. The Paradox comprises two questions. The first is why larger animals exhibit the same tumor risk as smaller animals. The second is why those with greater longevity do not have a higher cancer risk than more ephemeral species. The Paradox has appeared so elusive as it has been often assumed that any single explanation must account for both phenomena simultaneously. In reality Peto’s paradox comprises two problems with two distinct solutions.